Comparative Transcriptome Analysis in Homo- and Hetero-Grafted Cucurbit Seedlings - Bantis, Filippos; Tsiolas, George; Mouchtaropoulou, Evangelia; Tsompanoglou, Ioanna; Polidoros, Alexios N.; Argiriou, Anagnostis; Koukounaras, Athanasios (Frontiers in Plant Science, 2021)
Watermelon (Citrullus lanatus) is a valuable horticultural crop with nutritional benefits grown worldwide. It is almost exclusively cultivated as grafted scions onto interspecific squash rootstock (Cucurbita maxima × Cucurbita moschata) to improve the growth and yield and to address the problems of soilborne diseases and abiotic stress factors. This study aimed to examine the effect of grafting (homo- and hetero-grafting) on the transcriptome level of the seedlings. Therefore, we compared homo-grafted watermelon (WW) with non-grafted watermelon control (W), homo-grafted squash (SS) with non-grafted squash control (S), hetero-grafted watermelon onto squash (WS) with SS, and WS with WW. Different numbers of differentially expressed genes (DEGs) were identified in each comparison. In total, 318 significant DEGs were detected between the transcriptomes of hetero-grafts and homo-grafts at 16 h after grafting. Overall, a significantly higher number of downregulated transcripts was detected among the DEGs. Only one gene showing increased expression related to the cytokinin synthesis was common in three out of four comparisons involving WS, SS, and S. The highest number of differentially expressed (DE) transcripts (433) was detected in the comparison between SS and S, followed by the 127 transcripts between WW and W. The study provides a description of the transcriptomic nature of homo- and hetero-grafted early responses, while the results provide a start point for the elucidation of the molecular mechanisms and candidate genes for the functional analyses of hetero-graft and homo-graft systems in Cucurbitaceae and generally in the plants.